Disability, mental health, sexual orientation and gender identity: understanding health inequity through experience and difference - N. Nakkeeran; Barathi Nakkeeran (BMC, 2018)
Abstract Background This paper focuses on inequities in health in the context of disability, mental health, sexual orientation and gender identity (The authors' location outside of these identities is acknowledged as a serious limitation in discussing experience as a framework to understand health inequity in the dimensions of disability, mental health, sexual orientation and gender identity). These are dimensions that lead to health inequity primarily through the pathways of stigma and discrimination. The aim here is to distinguish the unique characteristics of these groups and thereby try and articulate a new understanding of health and health equity with identity and difference in the foreground. We aim to bring attention to experience as a crucial parameter to discuss health equity in this context. Discussion Health inequity can be approached in two ways. One is to look at the lacuna in the current public health discourse in addressing the specific health concerns along the dimensions of disability, mental health, sexual orientation and gender identity. The second approach involves a more organic way of taking on board the concerns of these groups, rather than as after-thoughts; this involves a framework that gives a central role to the lived experience of stigma and discrimination. The dimensions of disability, mental health, sexual orientation and gender identity affect health inequities constitutively, instrumentally through co-morbidities, and through stigma either directly or indirectly. Experience of stigma also forms the basis of identities and the difference between identities, which emerges as an important concept in the articulation of health inequities beyond measurable gaps. Recognition and representation of these differences then form the basis of an inclusive articulation on health. Conclusion The centrality of difference and experience prompts us to problematise the idea of equity that rests on 'avoidable and unfair', 'differentials' and even to argue that such a definition based on differentials, used in a quantitative sense, seriously limits our understanding of health inequity. Health equity will therefore not merely mean 'closing avoidable health gaps,' but mandate an inclusive social arrangement that celebrates difference.